2022
DOI: 10.1111/ffe.13689
|View full text |Cite
|
Sign up to set email alerts
|

Fuzzy inference system for failure strength estimation of plain and notched 3D‐printed polylactide components

Abstract: A fuzzy sets based computational fuzzy inference system has been used to estimate the failure strength of 3D‐printed polylactide components. The research has confirmed and validated the accuracy and reliability of this approach with a satisfying level of reliability. As far as failure strength is concerned, the following two types of input parameters have been considered: (i) manufacturing variables (i.e., manufacturing angle, infill density, and size of manufacturing voids) and (ii) geometrical features (i.e.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(21 citation statements)
references
References 23 publications
0
21
0
Order By: Relevance
“…In light of the unique features of 3D printed materials, over the last decade, the Sheffield Structural Integrity Research Group has run a number of experimental/ theoretical projects to assess whether the TCD is successful in assessing the static [38][39][40][41][42][43] and fatigue [44][45][46] strength of notched/flawed 3D printed materials. In what follows, some specific outcomes from this body of systematic research work will be reviewed and revisited by focusing attention specifically on polymers and concrete.…”
Section: Additively Manufactured Polymers and Concretementioning
confidence: 99%
“…In light of the unique features of 3D printed materials, over the last decade, the Sheffield Structural Integrity Research Group has run a number of experimental/ theoretical projects to assess whether the TCD is successful in assessing the static [38][39][40][41][42][43] and fatigue [44][45][46] strength of notched/flawed 3D printed materials. In what follows, some specific outcomes from this body of systematic research work will be reviewed and revisited by focusing attention specifically on polymers and concrete.…”
Section: Additively Manufactured Polymers and Concretementioning
confidence: 99%
“…Furthermore, when it comes to objects printed flat on the build plate, the mechanical behavior depends on the manufacturing raster angle 19,23,24 . This is because, by changing the manufacturing raster angle, the strength performance of the printed objects vary based on the average layer adhesion and the ultimate tensile strength of the 3D‐printed material 25,26 . Specifically, Weake et al 27 found that the tensile strength of an acrylonitrile butadiene styrene (ABS) part could be up to 150% higher when the applied force is parallel to the material filaments (manufacturing angle equals to 0°) than perpendicular (manufacturing angle equals to 90°).…”
Section: Introductionmentioning
confidence: 99%
“…Typical data‐driven methods, including artificial neural networks (ANN), fuzzy inference system (FIS), and other techniques, are widely applied to study the mechanical behavior of 3D‐printed object 27,29 . The complexity caused by the joint effect of multiple parameters is seen to be effectively solved by the application of nonlinear regression solutions included in the aforementioned techniques 26 . Specifically, compared with ANN—a “black box” structure, FIS framework has a “grey box” structure which benefits from its fuzzy rules, allowing more user control through the relatively transparent structure.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations